THE DEVELOPMENT OF PHYSICS LEARNING RESEARCH WITH STEM APPROACH IN INDONESIA: A CONTENT ANALYSIS - Dewi Fairuz Zulaikha; Jumadi Jumadi; Annisaa' Mardiani; Baiq Armita Lutfia (EDUSAINS, 2021)
THE DEVELOPMENT OF PHYSICS LEARNING RESEARCH WITH STEM APPROACH IN INDONESIA: A CONTENT ANALYSISAbstractThis study aims to provide an overview of physics learning research with the STEM approach in Indonesia. This study used a thematic content analysis method which aims to determine the depth of the study using a certain matrix so that a conclusion can be presented based on similarities and differences. This study analyzed SINTA indexed scientific articles published from 2016-2020. The results of the search were obtained as many as 51 scientific articles according to the scope of the research. Research that is mostly done is experiments. The most widely used number of samples was 11-30 and the type of sample that was most studied was students in class XI in Senior High School. The most widely used data collection instrument is the test instrument. The most popular physics material is temperature and heat material, while the most measured research variable is students' understanding of concepts. The product that is mostly developed in learning with the STEM approach is students’ worksheets, while the learning model that is most often integrated with the STEM approach is Project-Based Learning (PjBL). In the future, research should examine the effects of learning physics using the STEM approach on variables that are still rarely studied, such as students' representational abilities. In addition, it is necessary to apply a STEM learning approach to other materials that are still rarely used. Thus, it can be concluded that this study has provided preliminary information for further research and policy determination on the STEM approach in physics learning.AbstrakTujuan penelitian ini adalah untuk memberikan tinjauan umum terkait penelitian pembelajaran fisika dengan pendekatan STEM di Indonesia. Penelitian ini menggunakan metode thematic content analysis yang bertujuan untuk menentukan kedalaman penelitian dengan menggunakan matriks tertentu sehingga dapat disajikan suatu kesimpulan berdasarkan kesamaan dan perbedaan. Penelitian ini menganalisis artikel ilmiah terindeks SINTA yang dipublikasikan dari 2016-2020. Hasil dari pencarian diperoleh sebanyak 51 artikel ilmiah yang sesuai dengan lingkup penelitian. Penelitian yang banyak dilakukan adalah penelitian eksperimen. Jumlah sampel yang paling banyak digunakan adalah sebanyak 11-30 dan jenis sampel yang paling banyak diteliti adalah peserta didik di kelas XI SMA/MA. Instrumen pengumpulan data yang paling banyak digunakan adalah instrumen tes. Materi fisika yang paling diminati adalah materi Suhu dan Kalor, sedangkan variabel penelitian yang paling banyak diukur adalah pemahaman konsep peserta didik. Produk yang paling banyak dikembangkan dalam pembelajaran dengan pendekatan STEM adalah LKPD, sementara model pembelajaran yang paling sering diintegrasikan dengan pendekatan STEM adalah Project Based Learning (PjBL). Ke depannya penelitian sebaiknya mengkaji efek pembelajaran fisika dengan menggunakan pendekatan STEM terhadap variabel yang masih jarang diteliti, seperti kemampuan representasi peserta didik. Selain itu, perlu diterapkan pendekatan pembelajaran STEM pada materi lain yang masih jarang digunakan. Dengan demikian, dapat disimpulkan bahwa penelitian ini telah memberikan informasi awal untuk penelitian dan penentuan kebijakan lebih lanjut tentang pendekatan STEM dalam pembelajaran fisika.